Predictions of forming limit curves of AA6014 aluminium alloy at room temperature - Bressan J.D.* (2020)
© 2020 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (https://creativecommons.org/licenses/by-nc-nd/4.0/) Peer-review under responsibility of the scientific committee of the 23rd International Conference on Material Forming.The aim of present work is to examine D-Bressan mathematical model to accurately predict the surface limit strains by the critical fast shear stress criterion of conventional AA6014 aluminium alloy sheets, after loading with non-linear strain paths at room temperature. Two kinds of limit strain curves can be plotted in the Map of Principal Surface Limit Strains (MPLS): the surface local necking limit, FLC-N, and the fast shear stress fracture limit curve FLC-S. D-Bressan´s critical shear stress criterion model combined with Barlat´s Yld 2000-2D yield criterion is proposed for theoretical prediction of FLC-S curve in sheet metal forming operations and were compared with experimental outcomes of AA6014. In order to calibrate the Bressan-Barlat macroscopic model, tensile tests at two different strain rates on specimens cut at 0o, 45o and 90o to the rolling direction and bulge test were carried out at room temperature to obtain the material coefficients of plastic anisotropy, strain and strain rate hardening law. Experimental bi-linear strain paths were carried out in specimens with 1.04 mm thickness by pre-stretching in uniaxial stress direction up to two strain levels before performing Nakajima testing experiments for obtaining the forming limit strain curves. D-Bressan critical fast shear stress modelling, combined with Barlat´s Yld 2000-2d yield function, predicted quite well both formability of AA6014 sheet as received and the reduced FLC-S after 10% and 20% uniaxial pre-stretching and bi-linear strain path. Comparisons of experimental FLC-S and predictions with Barlat´s Yld 2000-2D and Hill 79 yield criteria were analyzed and discussed. D-Bressan approach with Barlat´s Yld 2000-2d yield function, for exponent m=6, provided better fitting to the experimental FLC-S curves than D-Bressan model combined with Hill 79 yield function.